Hybrid motion/force control: a review. (18th October 2017) - Ortenzi, V.; Stolkin, R.; Kuo, J.; Mistry, M.
Abstract: This paper reviews hybrid motion/force control, a control scheme which enables robots to perform tasks involving both motion, in the free space, and interactive force, at the contacts. Motivated by the large amount of literature on this topic, we facilitate comparison and elucidate the key differences among different approaches. An emphasis is placed on the study of the decoupling of motion control and force control. And we conclude that it is indeed possible to achieve a complete decoupling; however, this feature can be relaxed or sacrificed to reduce the robot's joint torques while still completing the task. Graphical Abstract: